The Composition and Metabolic Phenotype of Neisseria gonorrhoeae Biofilms - Apicella, Michael A.; Steichen, Christopher T.; McEwan, Alastair G.; Cho, Christine; Falsetta, Megan L.; Ketterer, Margaret; Shao, Jianqiang; Hunt, Jason; Jennings, Michael P. (Frontiers in Microbiology, 2011)
N. gonorrhoeae has been shown to form biofilms during cervical infection. Thus, biofilm formation may play an important role in the infection of women. The ability of N. gonorrhoeae to form membrane blebs is crucial to biofilm formation. Blebs contain DNA and outer membrane structures, which have been shown to be major constituents of the biofilm matrix. The organism expresses a DNA thermonuclease that is involved in remodeling of the biofilm matrix. Comparison of the transcriptional profiles of gonococcal biofilms and planktonic runoff indicate that genes involved in anaerobic metabolism and oxidative stress tolerance are more highly expressed in biofilm. The expression of aniA, ccp, and norB, which encode nitrite reductase, cytochrome c peroxidase, and nitric oxide reductase respectively, is required for mature biofilm formation over glass and human cervical cells. In addition, anaerobic respiration occurs in the substratum of gonococcal biofilms and disruption of the norB gene required for anaerobic respiration, results in a severe biofilm attenuation phenotype. It has been demonstrated that accumulation of nitric oxide (NO) contributes to the phenotype of a norB mutant and can retard biofilm formation. However, NO can also enhance biofilm formation, and this is largely dependent on the concentration and donation rate or steady state kinetics of NO. The majority of the genes involved in gonococcal oxidative stress tolerance are also required for normal biofilm formation, as mutations in the following genes result in attenuated biofilm formation over cervical cells and/or glass: oxyR, gor, prx, mntABC, trxB, and estD. Overall, biofilm formation appears to be an adaptation for coping with the environmental stresses present in the female genitourinary tract. Therefore, this review will discuss the studies, which describe the composition and metabolic phenotype of gonococcal biofilms.